2020
DOI: 10.3390/molecules25040971
|View full text |Cite
|
Sign up to set email alerts
|

Benzoxazole Derivative K313 Induces Cell Cycle Arrest, Apoptosis and Autophagy Blockage and Suppresses mTOR/p70S6K Pathway in Nalm-6 and Daudi Cells

Abstract: Benzoxazole derivative K313 has previously been reported to possess anti-inflammatory effects in lipopolysaccharide-induced RAW264.7 macrophages. To date, there have been no related reports on the anticancer effects of K313. In this study, we found that K313 reduced the viability of human B-cell leukemia (Nalm-6) and lymphoma (Daudi) cells in a dose-dependent manner without affecting healthy peripheral blood mononuclear cells (PBMCs) and induced moderate cell cycle arrest at the G0/G1 phase. Meanwhile, K313 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…It was observed that some compounds based on benzoxazole have antituberculotic (Ertan-Bolelli et al 2016;Pytela and Klimešová 2011;Rana et al 2014a, b;Šlachtová and Brulíková 2018;Zhang et al 2018), or antimalarial (Ongarora et al 2015;Zhang et al 2018), or antiviral activity (Bernard et al 2014;Demmer and Bunch 2015;Jonckers et al 2012;Sattar et al 2020;Zhang et al 2018). Moreover, it was demonstrated that a large group of benzoxazole derivatives exert cytotoxic effect on some cancer cells such as breast cancer cells (MCF-7, MDA-MB-213, MDA-MB-231), lung cancer cells (A549, H1975, HCC827), liver cancer cells (HepG2), prostate cancer cells (PC3), colorectal cancer cells (HCT-116, HT-29), oral cancer cells (KB), melanoma cells (A375), and others (Bernard et al 2014;Chung et al 2015;Desai et al 2020;Giordano et al 2019;Han et al 2012;Kakkar et al 2018;Kakkar and Narasimhan 2019;Kumar et al 2002;Li et al 2015;Omar et al 2020;Reddy et al 2016;Reynolds et al 1999;Rida et al 2005;Sachweh et al 2015;Sato et al 2001;Sattar et al 2020;Sever et al 2021;Slotkin et al 2016;Ueki et al 1993Zhang et al 2018;Zhong et al 2020;Zi et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that some compounds based on benzoxazole have antituberculotic (Ertan-Bolelli et al 2016;Pytela and Klimešová 2011;Rana et al 2014a, b;Šlachtová and Brulíková 2018;Zhang et al 2018), or antimalarial (Ongarora et al 2015;Zhang et al 2018), or antiviral activity (Bernard et al 2014;Demmer and Bunch 2015;Jonckers et al 2012;Sattar et al 2020;Zhang et al 2018). Moreover, it was demonstrated that a large group of benzoxazole derivatives exert cytotoxic effect on some cancer cells such as breast cancer cells (MCF-7, MDA-MB-213, MDA-MB-231), lung cancer cells (A549, H1975, HCC827), liver cancer cells (HepG2), prostate cancer cells (PC3), colorectal cancer cells (HCT-116, HT-29), oral cancer cells (KB), melanoma cells (A375), and others (Bernard et al 2014;Chung et al 2015;Desai et al 2020;Giordano et al 2019;Han et al 2012;Kakkar et al 2018;Kakkar and Narasimhan 2019;Kumar et al 2002;Li et al 2015;Omar et al 2020;Reddy et al 2016;Reynolds et al 1999;Rida et al 2005;Sachweh et al 2015;Sato et al 2001;Sattar et al 2020;Sever et al 2021;Slotkin et al 2016;Ueki et al 1993Zhang et al 2018;Zhong et al 2020;Zi et al 2019).…”
Section: Introductionmentioning
confidence: 99%